SISTEM INFORMASI E-REKRUTMEN BERBASIS WEB PADA PT PHAROS INDONESIA - Fernandi, Renaldi; Dewayani, Ery (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
Human resources are individuals who work productively for an organization such as an institution or company in an effort to achieve organizational goals that act as a driver and have value as assets for the organization so that their capabilities need to be improved and developed. Considering that human resources have a very large contribution to the company in achieving its goals and are an important capital asset for the company, therefore, a web-based e-recruitment information system in the process of recruiting and selecting prospective workers is needed by PT Pharos Indonesia to obtain qualified and competent human resources. The development of this e-recruitment information system uses the Waterfall System Development Life Cycle (SDLC) methodology. The database used by this application uses the MySQL database. The programming languages used are Golang and Javascript with the ReactJS Framework. Web-based e-recruitment information system can improve the recruitment process at PT Pharos Indonesia. Processing prospective employee data becomes easier, faster, and more accurate because prospective employee data is processed by computerization